2010
DOI: 10.1021/pr900962c
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Quantitative Proteomics Reveals Multiple Pathway Cross-Talk That Coordinates Specific Signaling and Transcriptional Regulation for the Early Host Response to LPS

Abstract: Toll-like receptor 4 (TLR4) specifically recognizes lipopolysaccharide (LPS) to initiate signal transduction events that modulate host inflammatory responses. Although increasing numbers of genes have been characterized individually for their involvement in TLR4 signaling, the LPS-induced TLR4-mediated signaling pathway and connected networks are incompletely delineated. Given that most components of signaling pathways are activated at an early phase of the LPS-induced response, we have employed a subcellular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 105 publications
1
28
0
Order By: Relevance
“…13 One study investigated changes in the kinase profile when macrophages were infected with Staphylococcus aureus , 14 while another compared the changes in protein expression with mRNA regulation in response to LPS, with the data indicating crosstalk between multiple pathways. 15 Although comparative transcriptome studies of the different TLR pathways have been published, 1618 there are very few phosphoproteomic studies targeted toward any of the other TLRs 19 and there have been no studies that compared the global phosphoprotein signatures of different TLRs. As bacterial and other microbial pathogens generally trigger a combination of TLRs, 5,20 deciphering the comprehensive signaling pathways of multiple TLRs is a critical step toward characterizing the response of a macrophage to the complex stimuli originating from pathogens during infection.…”
Section: Introductionmentioning
confidence: 99%
“…13 One study investigated changes in the kinase profile when macrophages were infected with Staphylococcus aureus , 14 while another compared the changes in protein expression with mRNA regulation in response to LPS, with the data indicating crosstalk between multiple pathways. 15 Although comparative transcriptome studies of the different TLR pathways have been published, 1618 there are very few phosphoproteomic studies targeted toward any of the other TLRs 19 and there have been no studies that compared the global phosphoprotein signatures of different TLRs. As bacterial and other microbial pathogens generally trigger a combination of TLRs, 5,20 deciphering the comprehensive signaling pathways of multiple TLRs is a critical step toward characterizing the response of a macrophage to the complex stimuli originating from pathogens during infection.…”
Section: Introductionmentioning
confidence: 99%
“…In the most comprehensive proteome-wide quantitative study using SILAC and subcellular fractionation, Du et al revealed signaling and regulatory networks that systematically operate in the early response to LPS (19). Weintz et al and Sharma et al performed quantitative phosphoproteome analyses upon LPS treatment, identifying a highly dynamic phosphorylation pattern in established signaling routes and beyond that could be linked to kinases operating in canonical TLR pathways, but also in the cell cycle (ATM/ATR kinases) and cell growth (mTOR) (13,14).…”
mentioning
confidence: 99%
“…The resulting fractions were then separated via SDS-PAGE, and gel slices were subjected to tryptic digestion and peptide extraction, followed by a LC-MS/MS analysis performed in two replicates ( Fig and 2B). Based on previous criteria and the quality of MS data with a higher signal-to-noise ratio, a threshold of a 20% change in protein abundance [33,34] (a light-to-heavy ratio of >1.2 or <0.8) was used to define whether a protein was differentially expressed. A total of 1,291 DEPs were identified with high confidence based on this threshold.…”
Section: Silacomics Identification Of the Grx1 Regulation Networkmentioning
confidence: 99%